Introduction to nutrition and metabolism - Bender, David A (London UCL press, 1993)
"Introduction to Nutrition and Metabolism equips readers with an understanding of the scientific basis of what we call a healthy diet. Now in its sixth edition, this highly recognized textbook provides clear explanations of how nutrients are metabolized and gives explains the principles of biochemistry needed for comprehending the science of nutrition. This full-color textbook explores the need for food and the uses to which food is put in the body, as well as the interactions between health and diet. Outlining the scientific basis behind nutritional requirements and recommendations, this new edition has been extensively revised to reflect current knowledge"--
Why eat? -- Enzymes and metabolic pathways -- The role of ATP in metabolism -- Digestion and absorption -- Energy nutrition : the metabolism of carbohydrates and fats -- Diet and health : nutrition and chronic non-communicable diseases -- Overweight and obesity -- Protein-energy malnutrition : problems of undernutrition -- Protein nutrition and metabolism -- The integration and control of metabolism -- Micronutrients : the vitamins and minerals.
Keywords: Nutritional Physiological Phenomena; Metabolism